Parameterized algorithmics for d-Hitting Set - Fernau, Henning (International journal of computer mathematics, 2010)
Based on the methodology we presented in earlier work on parameterized algorithms for 3-Hitting Set, we develop simple search tree-based algorithms for d-Hitting Set. We considerably improve on the bounds that were elsewhere derived for these problems.